ANAK PUTUS SEKOLAH PADA MASYARAKAT MARGINAL DI PERKOTAAN ( Studi terhadap masyarakat di Kelurahan Meranti Pandak Kecamatan Rumbai Pesisir Kota Pekanbaru) - Agus Setiawan; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Research on children who drop in marginal communities in urban areas isdone in Kelurahan Meranti Pandak Pekanbaru city of Riau Province. This study aimsto investigate the phenomenon of drop outs in marginal areas, the ground dropped outof school, drop out of school activities, perceptions of parent. Qualitative method areused namely, with a population of 112 people, considering the total populationenough, so sampling techniques performed by means of random sampling tecniquesto select 20% the populations of 22 people refresentatif. Collection of research dataobtaiined by the method of interview, observation and documentation.Tecniqueanalysis of the data used is descriptive analysis complete with percentages. Based onthe result of the research we can conclude that the causes children dropouts villageMeranti Pandak because the own accord 40,90% to be dominant factor, economicfactors family 31,83% and environmental factors a playmate 27,27%. Are children isworking 45,5% of being predominant, activity help parents 36,6% and unemployment18.2%. The majorityof his parents for lack of good 45,5%. This writer is better for agiven understanding to increase the motivation to school by parents and societyenvironment,Keywords: Children dropouts,Marginal Society and Meranti Pandak